2018
DOI: 10.1111/bph.14513
|View full text |Cite
|
Sign up to set email alerts
|

OSCP subunit of mitochondrial ATP synthase: role in regulation of enzyme function and of its transition to a pore

Abstract: The permeability transition pore (PTP) is a latent, high‐conductance channel of the inner mitochondrial membrane. When activated, it plays a key role in cell death and therefore in several diseases. The investigation of the PTP took an unexpected turn after the discovery that cyclophilin D (the target of the PTP inhibitory effect of cyclosporin A) binds to FOF1 (F)‐ATP synthase, thus inhibiting its catalytic activity by about 30%. This observation was followed by the demonstration that binding occurs at a part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 97 publications
(145 reference statements)
3
31
0
Order By: Relevance
“…The top of the peripheral stalk flexes only slightly. Previous studies have suggested that the interdomain region of OSCP may be flexible (17)(18)(19). In comparing all 13 substates, no coiling of the central stalk is apparent ( fig.…”
Section: High-resolution Map Of a Complete F-type Atp Synthase Dimermentioning
confidence: 80%
“…The top of the peripheral stalk flexes only slightly. Previous studies have suggested that the interdomain region of OSCP may be flexible (17)(18)(19). In comparing all 13 substates, no coiling of the central stalk is apparent ( fig.…”
Section: High-resolution Map Of a Complete F-type Atp Synthase Dimermentioning
confidence: 80%
“…Tight coupling between F 1 and F O subcomplexes is required for highly efficient rotational catalysis and occurs through two stalks, the F 1 central stalk (consisting of γ, δ, ɛ subunits in mitochondria) and the F O peripheral stalk (primarily consisting of OSCP, b, h, d subunits) [76,78,79]. OSCP connects F O with F 1 through the peripheral stalk and is an important site of modulation of ATP synthase leak channel activity due to its interaction with different endogenous and pharmacological inducers of mPTP [80][81][82]. During the mPT initiation step, mPTP modulators bind directly to different ATP synthase subunits: CypD binds to OSCP subunit [83][84][85] and Ca 2+ binds to β subunit [63,64] ( Fig.…”
Section: The Molecular Composition Of Mptp: Atp Synthase C-subunit Rimentioning
confidence: 99%
“…The structural and functional coupling between F O and F 1 in the mature complex is mainly guaranteed by the OSCP or δ subunit in mitochondria and in bacteria, respectively. Through its contacts with both the α 3 β 3 hexamer and the peripheral stalk, OSCP or δ prevents corotation of the αβ dimers with the γ subunit, thereby ensuring very high enzyme efficiency [25]. Another domain crucial for the functional coupling is located at the C-terminus of β subunit, which is in direct contact with γ subunit, termed the DELSEED loop, which is thought to transfer the torque to γ from the nucleotide binding domain [26].…”
Section: F-type Atp Synthase As a Molecular Motormentioning
confidence: 99%
“…Nevertheless, the Ca 2+ - and ROS-dependent long-range conformational changes that could be responsible for the PTP formation in the F O sector remain to be defined. Moreover, other models of PTP have been advanced that hypothesize the PTP resides in the c -ring of ATP synthase [76, 79] or, alternatively, in some other mitochondrial components not involving ATP synthase [86] so that its molecular nature is still a matter of debate [25].…”
Section: F-atp Synthase Uncouplingmentioning
confidence: 99%